Cover Feature: Fluorescent Imidazo[1, 2‐a]pyrimidine Compounds as Biocompatible Organic Photosensitizers that Generate Singlet Oxygen: A Potential Tool for Phototheranostics (Chem. Eur. J. 20/2021). Issue 20 (3rd February 2021) - Lima, Maria L. S. O.; Braga, Carolyne B.; Becher, Tiago B.; Odriozola‐Gimeno, Mikel; Torrent‐Sucarrat, Miquel; Rivilla, Iván; Cossío, Fernando P.; Marsaioli, Anita J.; Ornelas, Catia
Abstract : Fluorescent tetracyclic imidazo[1, 2‐ a ]pyri(mi)dines can be generated by microwave‐assisted high order (8+2) thermal cycloadditions between in situ formed benzynes and the corresponding bicyclic imidazo[1, 2‐ a ]pyr(im)idines. These cycloadducts absorb and emit photons in the 400‐500 nm region and are efficiently uptaken by cells with low cytotoxicity. Upon irradiation, these molecules generate singlet oxygen and are able to kill cancer cells at low concentration, thus emerging as promising candidates for photodynamic therapy and fluorescence imaging. . More information can be found in the Full Paper by A. J. Marsaioli, C. Ornelas, et al. on page 6213 .